Environmental chemistry and health: a vital nexus / Shahida Hanum Kamarullah and Nur Sha'adah Zainuddin - Kamarullah, Shahida Hanum; Zainuddin, Nur Sha'adah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
In the modern world, the intricate interactions between environmental chemistry and human health have become of the utmost significance. The study of environmental chemistry focuses on the chemical reactions and processes that occur in the soil, water, air, and ecosystems. Comprehending the influence of environmental elements on human well-being is essential for managing a range of health issues. The following section will explore the relationship between environmental chemistry and health.